Transaksi dan Kontrak Jual Beli Makanan pada Layanan Gofood; Analisis Hukum Islam dan Hukum Positif - Jessy R. A Indriati; Rina Susanti Abidin Bahren; Hisyam Asyiqin (IAIN Langsa, 2025)
This research aims to analyze food purchase transactions and contracts through the GoFood service from the perspective of Islamic Law and Positive Law, focusing on the conformity of contracts in practice with sharia principles as well as legality based on Indonesian laws and regulations. This article falls under qualitative library research with a normative legal study methodology. The findings indicate that transactions conducted through GoFood are essentially valid under Islamic law as long as the requirements and pillars of sale and purchase are fulfilled, such as the presence of a seller, a buyer, a clear object, and mutual consent, even if the contract is made electronically. Meanwhile, under Indonesia’s positive law, such transactions are considered valid and legally binding based on Law Number 11 of 2008 concerning Electronic Information and Transactions and its implementing regulations. Nevertheless, there remain issues related to the clarity of contracts, transparency of product information, and consumer protection, which require stronger regulations and stricter application of sharia principles.